Reactions of a diborylstannylene with CO2 and N2O: diboration of carbon dioxide by a main group bis(boryl) complex. Issue 26 (11th May 2021) - Protchenko, Andrey V.; Fuentes, M. Ángeles; Hicks, Jamie; McManus, Caitilín; Tirfoin, Rémi; Aldridge, Simon
Abstract : Reactions of a bis(boryl) tin complex towards carbon dioxide proceed via insertion into the Sn–B bond(s), with subsequent B–O reductive elimination leading to the net diboration of CO2 . Abstract : The reactions of the boryl-substituted stannylene SnB(NDippCH)2 2 (1 ) with carbon dioxide have been investigated and shown to proceed via pathways involving insertion into the Sn–B bond(s). In the first instance this leads to formation of the (boryl)tin(ii ) borylcarboxylate complex SnB(NDippCH)2 O2 CB(NDippCH)2 (2 ), which has been structurally characterized and shown to feature a κ 2 mode of coordination of the [(HCDippN)2 BCO2 ] − ligand at the metal centre. 2 undergoes B–O reductive elimination in hexane solution (in the absence of further CO2 ) to give the boryl(borylcarboxylate)ester (HCDippN)2 BO2 CB(NDippCH)2 (3 ) i.e. the product of formal diboration of carbon dioxide. Alternatively, 2 can assimilate a second equivalent of CO2 to give the homoleptic bis(borylcarboxylate) SnO2 CB(NDippCH)2 2 (4 ), which can be prepared via an alternative route from SnBr2 and the potassium salt of [(HCDippN)2 BCO2 ] −, and structurally characterized as its DMAP ( N, N -dimethylaminopyridine) adduct. Structural and reactivity studies also point to the possibility for extrusion of CO from the [(HCDippN)2 BCO2 ] − fragment to generate the boryloxy system [(HCDippN)2 BO] −, a ligand which can be generated directly from 1 via reaction with N2 O. The initially formed unsymmetrical species SnB(NDippCH)2 OB(NDippCH)2 has been shown to be amenable to crystallographic study in the solid state, but to undergo ligand redistribution in solution to generate a mixture of 1 and the bis(boryloxy) complex SnOB(NDippCH)2 2 .